Pengaruh Profitabilitas dan Likuiditas Terhadap Modal Kerja pada Perusahaan Hotel Restoran dan Pariwisata yang Terdaftar di Bursa Efek Indonesia - Nurwani Nurwani (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
The purpose of this research was to examine the influence and analyze of profitability and liquidity on working capital partially and simultaneously. The population of this research was 35 hotel, restaurant, and tourism companies listed in the Indonesia Stock Exchange in the period of 2017-2019 and samples of 12 companies by using purposive sampling technique. The data were processed by using multiple linear regression analysis. The result of the research showed that first, profitability had influence positive and significant on working capital. Secondly showed that liquidity had influence positive and insignificant on working capital. Thirdly showed that profitability and liquidity influence significant on working capital simultaneously